Reciprocal longitudinal associations between substance use and child‐to‐parent violence in adolescents. (11th August 2015) - Calvete, Esther; Orue, Izaskun; Gámez‐Guadix, Manuel
Abstract: Child‐to‐parent violence (CPV) is a type of violence that has received little attention despite its increasing rates in Western countries. Several models state that substance abuse constitutes a risk factor for aggressive behavior and that relationships among these variables can be reciprocal. In this study, the temporal relationships among substance use and physical and psychological CPV were examined. A sample of 981 adolescents (mean age = 15.22 years, SD = 1.2 years) completed measures of substance use and CPV at three time points (T1, T2, and T3) spaced 6 months apart. The results indicated that T1 levels of substance use predicted an increase in psychological CPV at T2 and that T2 levels of substance use predicted an increase in physical CPV at T3. Additionally, several mediational mechanisms emerged between substance use at T1 and CPV at T3. Neither physical nor psychological CPV predicted an increase in substance use at any time. Multiple comparisons indicated that the predictive association between substance use and physical aggression against parents was significant only in boys. These findings suggest that preventive programs for CPV should include specific components for reducing substance use.